Deformation behaviour of glass fibre reinforced concrete containing palm oil fuel ash - Awal, A. S. M. A. (2014)
Palm oil fuel ash (POFA) has been known to be a good pozzolanic material and played an effective role in improving the physical and mechanical properties of concrete. This paper highlights the results obtained from the laboratory tests on compressive strength, modulus of elasticity, creep and shrinkage of glass fibre reinforced concrete (GFRC) containing POFA. Concrete specimens of grade 30 was designed following DoE method where GFRC with 0.5% fibre content was prepared with OPC replaced by 20% POFA by weight. Laboratory tests based on short-term investigation showed that the modulus of elasticity of GFRC containing POFA in association with its compressive strength was slightly lower than that of concrete without POFA. The measured values of creep and shrinkage, however, revealed that the creep and shrinkage strain of GFRC containing POFA were higher than that of concrete with OPC alone. On the basis of short-term investigation, the one-year creep and shrinkage values of both types of concrete were also predicted by extrapolating the data obtained in this study.